Incidence, Diagnosis, and Management of QT Prolongation Induced by Cancer Therapies: A Systematic Review. Issue 12 (7th December 2017) - Porta‐Sánchez, Andreu; Gilbert, Cameron; Spears, Danna; Amir, Eitan; Chan, Joyce; Nanthakumar, Kumaraswamy; Thavendiranathan, Paaladinesh
Abstract : Background: The cardiovascular complications of cancer therapeutics are the focus of the burgeoning field of cardio‐oncology. A common challenge in this field is the impact of cancer drugs on cardiac repolarization (ie, QT prolongation) and the potential risk for the life‐threatening arrhythmia torsades de pointes. Although QT prolongation is not a perfect marker of arrhythmia risk, this has become a primary safety metric among oncologists. Cardiologists caring for patients receiving cancer treatment should become familiar with the drugs associated with QT prolongation, its incidence, and appropriate management strategies to provide meaningful consultation in this complex clinical scenario. Methods and Results: In this article, we performed a systematic review (using Preferred Reporting Items of Systematic Reviews and Meta‐Analyses (PRISMA) guidelines) of commonly used cancer drugs to determine the incidence of QT prolongation and clinically relevant arrhythmias. We calculated summary estimates of the incidence of all and clinically relevant QT prolongation as well as arrhythmias and sudden cardiac death. We then describe strategies to prevent, identify, and manage QT prolongation in patients receiving cancer therapy. We identified a total of 173 relevant publications. The weighted incidence of any corrected QT (QTc) prolongation in our systematic review in patients treated with conventional therapies (eg, anthracyclines) ranged from 0% to 22%, although QTc >500 ms, arrhythmias, or sudden cardiac death was extremely rare. The risk of QTc prolongation with targeted therapies (eg, small molecular tyrosine kinase inhibitors) ranged between 0% and 22.7% with severe prolongation (QTc >500 ms) reported in 0% to 5.2% of the patients. Arrhythmias and sudden cardiac death were rare. Conclusions: Our systematic review demonstrates that there is variability in the incidence of QTc prolongation of various cancer drugs; however, the clinical consequence, as defined by arrhythmias or sudden cardiac death, remains rare.